Deficit finance during the early majority of Henry VI of England, 1436-1444: The "crisis" of the medieval English "tax state" - Alex Brayson (The Journal of European Economic History, 2020)
This article takes a radically new approach to the fiscal collapse of the Lancastrian state prior to the Wars of the Roses. Whereas previous studies have sought to locate the origins of the infamous 372,000 royal debt declared before parliament in 1449-50 in the short-term fiscal political context of Henry VI's troubled kingship during the late 1440s, the present article documents the development of a longer-term structural crisis in the public finances. During the conciliar rule of Henry VI's early majority in the late 1430s and early 1440s, parliamentary-controlled income declined markedly as a result of historically low indirect tax yields and MPs' unwillingness, at a time of growing socio-economic problems, to respond to the king's personal fiscal overtures and grant the required level of compensatory lay taxation to fund heavy expenditures. Consequently, a mounting deficit characterised all areas of the royal budget, whilst the total deficit doubled. As affairs of state gravitated towards Henry VI's court around 1444, total debt was already well in excess of 300,000. Viewed in the context of R.J. Bonney and W.M. Ormrod's "new" fiscal historiography, these developments signify that the political and economic limits of the medieval English "tax state" had been reached, thus paving the way for a structural fiscal regression to a low-yield "domain" state from the 1450s.
Keywords: 330